The effects of age, sex, and habitat on body size and shape of the blackstripe topminnow, Fundulus notatus (Cyprinodontiformes: Fundulidae) (Rafinesque 1820). (25th January 2013) - Welsh, Daniel P.; Zhou, Muchu; Mussmann, Steven M.; Fields, Lauren G.; Thomas, Claire L.; Pearish, Simon P.; Kilburn, Stephanie L.; Parker, Jerrod L.; Stein, Laura R.; Bartlett, Jennifer A.; Bertram, Christopher R.; Bland, Thomas J.; et al.
<x xml:space="preserve">Abstract</x> Lake and stream habitats pose a variety of challenges to fishes due to differences in variables such as water velocity, habitat structure, prey community, and predator community. These differences can cause divergent selection on body size and/or shape. Here, we measured sex, age, length, and eight different morphological traits of the blackstripe topminnow, Fundulus notatus, from 19 lake and stream populations across four river drainages in central Illinois. Our goal was to determine whether size and shape differed consistently between lake and stream habitats across drainages. We also considered the effects of age and sex as they may affect size and morphology. We found large differences in body size of age 1 topminnows where stream fish were generally larger than lake fish. Body shape mainly varied as a function of sex. Adult male topminnows had larger morphological traits (with the exception of body width) than females, in particular longer dorsal and anal base lengths. Subtle effects of habitat were present. Stream fish had a longer dorsal fin base than lake fish. These phenotypic patterns may be the result of genetic and/or environmental variation. As these lakes are human‐made, the observed differences, if genetic, would have had to occur relatively rapidly (within about 100 years). © 2013 The Linnean Society of London